Enhancing Counselors' Skills In Developing Non-Test Instruments Independently - Lubis, Khadijah; Dewi, Ratna Sari; Wisma, Nur; Sucipto, Sigit Dwi; Rozzaqyah, Fadhlina; Hafarinto, Bagus; Alfaroji, Muhammad Arif (International Journal of Public Devotion, 2024)
Non-test instruments are fundamental in the implementation of student needs assessment. Without the right instruments, the assessment will not be able to be carried out and the implementation of guidance and counseling services will not be able to reach services that are by student needs. This requires counselors to be able to develop instruments that can measure the psychological condition of students which can be used as a reference for making programs and providing services for students. But in reality, counseling teachers are still confused, unable to make instruments, and limited to processing and analyzing the results of the instruments obtained so that the counseling program prepared later is by the needs of students.This training and mentoring activity aims to assist counselors in developing non-test instruments independently. This activity was carried out for 9 days for Palembang City Junior High School counselors who were organized in the Palembang City Junior High School MGBK. The implementation of this activity was carried out using discussion, brainstorming, practice, and assignment methods. This activity began with filling out pretests, providing material, practice, and assignments, analyzing data, interpreting data, and ending with filling out posttests. The results of the pretest and posttest data analysis showed that the t-test significance value obtained was 0.001 <0.05, which means that there is a significant difference in the skills of counseling teachers in preparing non-test instruments before and after attending the training. During the activity, counselors were enthusiastic and eager to participate in the training. The output of this training is a questionnaire that can be used in their respective schools to assess students' needs.